Handball for life (5th EHF Scientific Conference "Handball for Life", 21.-22.11.2019, Cologne, 2020)
- Póvoas (POR) "The handball 4 health project - implementation, dissemination and research" - Dias Estriga (POR) "The effect of resin and ball size on the throwing velocity" - Gheorghe; Mereuta (ROU) "The impact of a top player injury on Romanian National handball team performance at the France EHF EURO 2018" - Gillard; Romenskaya (RUS) "Differences in attention attributes for female handball players" - Gillard (RUS) "Features injuries handball players 18-20 years old in competition" " Gonzaga; Sequeira (POR) "Coaches' emotional skills and interpersonal behaviours in sports coaching" - Hermassi et al. (TUN) "Effects of training specificity into influencing agility and sprint performance of team handball players" - Karcher et al. (FRA) "Determinants of shooting velocity in elite team handball players" - Nicklas et al. (GER) "Effects of blocking on defense performance in beach handball" - Ökros (HUN) "Load parameters associated with Qatch matches using microsensor technology" - Sequeira; Erichsen (POR) "E-Handball: Technology helps development" - Sequeira; Lopes (POR) "E-Sports: Handball New Challenge" - Slowinski (POL) "The referee's age and experience versus the accuracy of handball referee decisions at various levels of competition" - Souli; Gillard (RUS) "Peculiarities of motivation in the activity of professional handball players" - Wilhelm et al. (GER) "Fouls in women's team handball - the effect of a permitted foul on defense performance" - Dias Estriga; Ferreira (POR) "Implications of a linear force-velocity relation on complex movements. A preliminary study with throwing" - Fukuda et al. (JPN) "Effect of ankle taping on knee and hip joint angles during jump landing tasks" - Gillard; Boussaha (RUS) "Conflictometric analysis of interpersonal relations in women's handball team" - Hodic (CRO) "Physiotherapy and rehabilitation in professional sports" - Hodic (CRO) "The most common injuries in team sports and their early rehabilitation with the use of orthopaedic sport supports" - Ichimura et al. (JPN) "Development of statistical data index for evaluating the tactical aspects of attack and defense in handball" - Ito et al. (JPN) "Kinematic analysis of throwing for handball player the difference between using sticking tape and the sticking gel" - Jelicic (CRO) "Injury, Prevention and recovery - psychological background and approach" - Lindenthal (GER) "Shot frequency and success rate of various types of throws from backcourt positions" - Mohoric; Sibila; Bon (SLO) "Motor and morphological differences between young female handball players from three age groups" - Moriguchi et al. (JPN) "Electroacupuncture (EA) treatment for top athletes in Japan a case of treatment of strained calf muscle in handball player" - Redlich; Fasold (GER) "What makes you win? - The perception of handball specific match situations" - Seipp et al. (GER) "Application of one-handed catches in elite men's team handball" - Skarbalius (LAT) "Quantification of monotony, weekly load and strain an entire competitive period in semi-professional female handball" - Suzuki et al. (JPN) "The effect of plyometric training on anterior cruciate ligament injury prevention and leg muscle strength in female junior handball players" - Further topics presented at the Scientific Conference (Abstracts)